ҚОРАҚАЛПОҚ ХАЛҚ ПЕДАГОГИКАСИ ВОСИТАЛАРИ ШАХС ТАЪЛИМ-ТАРБИЯСИДА МУҲИМ МАНБА СИФАТИДА - Досходжаева, А. (SCIENCE and SOCIETY, 2016)
The article contains the information about a person‘s spirituality and solution of ecological problems. The author emphasizes the importance of providing students with ecological knowledge and education, forming the ethic attitude to nature and environment, working out the skillful organization of conscious ecological activity in them.